Exploration of Phytochemicals Found in Terminalia sp. and their Antiretroviral Activities - Dwevedi, Alka; Dwivedi, Raman; Sharma, Yogesh K (Pharmacognosy Reviews)
The human immunodeficiency virus (HIV) infects cells of the immune system and destroys their function. Approximately, 2 million people die every year from HIV as reported by the World Health Organization. HIV/AIDS is difficult to treat as the virus continuously develops resistance to drugs being developed. Approach is now turning toward natural products for the development of anti-HIV drugs. Although HIV/AIDS is not a new disease, but research based on plant-derived products is still under clinical trials. Experimentally, it has been proven that plants have the potential for HIV treatment. The process involves identification of the active ingredients responsible for the reported anti-HIV activities, testing of the extract, and development of appropriate bioassays. Further development would require optimization of the formulation and manufacturing in compliance with preclinical safety and efficacy testing. The most challenging task for the natural product scientists is to separate these highly complex extracts containing several compounds into its individual components that are biologically active. Recently developed direct binding assay with mass spectrometry (MS) technology (viz., real-time time-of-flight-MS) is helpful in this respect but needs extensive optimization. At present, we have compiled all the information for the various phytochemicals present in Terminalia catappa having anti-HIV properties. These include tannins, gallotannins, ellagitannins, cyanidin, and flavonoids. Further, we have also discussed their pharmacological as well as pharmacokinetics studies.
Keywords: AIDS; flavonoids; human immunodeficiency virus; pharmacokinetics; pharmacology; tannins